The Long-Run Relationship between Disaggregated Government Expenditure and Economic Growth in Jordan - Alhaj Yousef, Elham Mohammad (International Journal of Economics and Financial Issues, 2022)
The main purpose of this study is to investigate the long run impact of capital and current government expenditures on the economic growth of Jordan during the period 1990-2019. The study variables are integrated of different orders as indicated by Augmented Dickey-Fuller unit root test. Granger causality test has demonstrated the ability of both government expenditure components to cause and predict changes in the economic growth. Engle and Granger cointegration test has revealed that there is a cointegrated long-run relationship between the study variables. Therefore, the study model was estimated by applying two estimation methods; Fully Modified Ordinary Least Squares (FMOLS) and Autoregressive Distributed lag (ARDL) models. The results of both methods showed that capital government expenditure has a significant positive long-run impact on the economic growth, while current expenditure has a significant negative long run impact on such growth according to FMOLS results. Based on these outcomes, the study recommends some procedures that must be implemented by the Jordanian government in order to increase its productive investments and reduce current expenditure.